Identification of a Six-Gene Prognostic Signature Characterized by Tumor Microenvironment Immune Profiles in Clear Cell Renal Cell Carcinoma - Zhang, Lu; Li, Jianlong; Zhang, Mengzhao; Wang, Lu; Yang, Tao; Shao, Qiuya; Liang, Xiao; Ma, Minghai; Zhang, Nan; Jing, Minxuan; Song, Rundong; Fan, Jinhai (Frontiers in Genetics, 2021)
Clear cell renal cell carcinoma (ccRCC) is widely acknowledged to be extremely sensitive to immunotherapy emphasizing the tremendous impacts on which the tumor microenvironment (TME) has shown. However, the molecular subgroups characterized by the TME features are scarcely served as the risk stratification guided in clinical practice for survival outcomes and immunotherapy response prediction. In this study, we generated fresh insights into a novel TME-related prognostic signature derived from the Cancer Genome Atlas (TCGA) database using the integrated bioinformatics analyses. Subsequently, the Kaplan Meier survival analysis, ROC analysis, univariate and multivariate Cox regression analysis were performed to evaluate and validate the efficacy and accuracy of the signature in ccRCC prognosis. Furthermore, we discovered that the risk score presented an increased likelihood of correlation with miscellaneous clinicopathological characteristics, Natural Killer (NK) cell mediated cytotoxicity, immune cell infiltration levels, and immune checkpoints expression. These findings highlighted the notion that the six-gene signature characterized by the TME features may have implications on the risk stratification for personalized and precise immunotherapeutic management.